Regenerated cellulose fiber based on gel spinning and preparation method and application thereof
Through the frozen glue spinning method, the cellulose raw material is dissolved using the LiCl/DMAc system and solidified at low temperature. Combined with high drafting magnification, the problem of insufficient mechanical properties of cellulose fibers in the prior art is solved, and the industrial production of regenerated cellulose fibers with high strength and high modulus is achieved.
Patent Information
- Application Number
- CN202510509340.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-07-22
AI Technical Summary
It is difficult to prepare regenerated cellulose fibers with excellent performance at low cost, especially straw cellulose fibers, which have problems such as many raw material impurities, low solution concentration, low crystallinity, poor orientation, and inability to meet industrial application requirements.
By using the frozen glue spinning method, regenerated cellulose fibers were prepared by dissolving the cellulose raw material in the LiCl/DMAc system after activation of water/DMAc dual solvent to form a spinning liquid with a concentration of 5 to 15 wt%, and a methanol solidification bath was performed at a temperature lower than the gel point of the spinning liquid. Regenerated cellulose fibers were prepared by combining high drafting ratio and solvent replacement, washing and drying.
The tensile strength of the prepared regenerated cellulose fibers reaches 664MPa, the modulus is 41GPa, and the fiber surface smoothness Ra≤0.1μm. It is suitable for industrial continuous production, and solves the problem of insufficient mechanical properties of cellulose fibers in the prior art.
Smart Images

Figure CN120350438A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of bio-based high performance, and particularly relates to a regenerated cellulose fiber based on gel spinning and a preparation method thereof, which is particularly suitable for the efficient conversion of two types of raw materials, namely microcrystalline cellulose and straw cellulose. Background Art
[0002] Cellulose widely exists in various plants and is the most abundant renewable biomass resource on the earth. For thousands of years, cellulose has been widely used in human life and production. Today, in the pursuit of green and sustainable development, the application prospect of cellulose, such a large-yield and renewable resource, has become even broader. Improving the utilization rate of cellulose, especially renewable resources such as straw, is an important way and direction for the sustainable green development of the national economy. Cellulose can be prepared into regenerated cellulose fibers, aerogels, membranes, etc., and applied to the textile industry, papermaking, biomass fuels, etc.
[0003] Regenerated celluloses in different geometric forms such as fibers, films, and aerogels require the dissolution and regeneration of cellulose. The dispersion state of cellulose chains is crucial for the structure and mechanical properties of regenerated cellulose. For example, Sameer et al. dissolved cellulose in a cellulose / 2-ethyl-3-methylimidazolium phosphate anhydride ([Emim]DEP) solution at 25 °C and 80 °C respectively, and then spun regenerated cellulose fibers, and observed the existence of the liquid crystal phase at 25 °C; the existence of the liquid crystal phase makes the modulus of the regenerated cellulose fiber 40% higher than that of the homogeneous solution. It has been reported that both heating and cooling can cause irreversible gelation of cellulose / NaOH / urea solutions.
[0004] Regenerated cellulose fibers are fibers with better mechanical properties obtained by dissolving cellulose in a certain way and then regenerating it from a coagulation bath. At present, there are some problems in the NMMO system for preparing cellulose, such as environmental pollution during the preparation process and low strength of the prepared cellulose. The emergence of ionic liquid solvents provides a new and versatile platform for the research on the effective utilization and high-value conversion of cellulose. However, at present, the research on the application of ionic liquids in cellulose chemistry is still in its initial stage, and some important technical problems have not been solved. For example, the synthesis cost of ionic liquids is high.
[0005] Therefore, how to prepare regenerated cellulose fibers with excellent properties at low cost is an urgent problem to be solved at present. Summary of the Invention
[0006] In view of the above problems, the present invention provides a regenerated cellulose fiber based on gel spinning and a preparation method thereof.
[0007] To solve the above technical problems, the present invention adopts the following technical solutions:
[0008] A preparation method of regenerated cellulose fiber based on gel spinning, comprising the following steps:
[0009] Step 1, activating the cellulose raw material with a water / DMAc double solvent and then dissolving it in a LiCl / DMAc system to form a spinning solution with a concentration of 5-15 wt%;
[0010] Step 2, extruding the solution through a gel spinning process into a methanol coagulation bath with a temperature lower than the gel point of the spinning solution, and the draw ratio ≥ 3 times;
[0011] Step 3, subjecting the nascent fiber to solvent replacement, washing, and drying to obtain the regenerated cellulose fiber.
[0012] Furthermore, the cellulose raw material is selected from microcrystalline cellulose MCC or straw cellulose;
[0013] Forming a spinning solution with a concentration of 5-15 wt%, wherein: the concentration of the microcrystalline cellulose spinning solution is 8-12 wt%, and when the draw ratio is 3 times, the fineness ≤ 10.81 dtex; the concentration of the straw cellulose spinning solution is 4-6 wt%.
[0014] Furthermore, the temperature of the coagulation bath in Step 2 is -60 °C.
[0015] Furthermore, in Step 1, the mass ratio of LiCl to DMAc in the LiCl / DMAc system is 1:11.5.
[0016] For the regenerated cellulose fiber based on gel spinning prepared by the above preparation method, the microcrystalline cellulose fiber: the tensile strength is 250-365 MPa, and the modulus is 18.5-41 GPa; the straw cellulose fiber: the tensile strength ≥ 664 MPa, the modulus ≥ 41 GPa, the surface roughness Ra of the fiber ≤ 0.2 μm, and the roundness index of the cross-section ≥ 0.80.
[0017] Furthermore, the 002 crystal plane spacing of the regenerated cellulose fiber ≤ 0.396 nm, the crystal size ≥ 38 nm, and the elongation at break ≥ 5%.
[0018] Furthermore, the tensile strength of the fiber ≥ 350 MPa, especially the tensile strength of the straw cellulose reaches 664 MPa, the modulus ≥ 18.5 GPa, the crystallinity ≥ 63%, and the orientation degree FWHM ≤ 21.76°.
[0019] Application of the regenerated cellulose fiber based on gel spinning in high-strength composite materials.
[0020] Application of the regenerated cellulose fiber based on gel spinning in aerospace structure reinforcements.
[0021] Application of the regenerated cellulose fiber based on gel spinning in biomedical sutures.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] Through raw material activation, low-concentration dissolution, low-temperature gel spinning in combination with high draw ratio, and structure-property regulation, the method of the present invention solves the problems that existing straw cellulose fibers have low fiber crystallinity (≤45%) and poor orientation (FWHM≥30°) due to a large amount of impurities in the raw materials and low solution concentration, resulting in mechanical properties that cannot meet the requirements of industrial applications.
[0024] The tensile strength of the regenerated cellulose fiber prepared by the present invention reaches 664 MPa (2.2 times that of viscose fiber), and the elastic modulus is 41 GPa; the fiber roundness index is 0.80, and the surface smoothness Ra≤0.1 μm (verified by SEM), which is suitable for industrial continuous production.
[0025] Compared with the ionic liquid IL solvent which is more expensive by more than 1 yuan / g, the DMAc / LiCl system used in the present invention is a very mature industrial product, which is cheap and can be recycled. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following will briefly introduce the drawings required for the description of the embodiments. Obviously, the following drawings are only some embodiments of the present application. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0027] Figure 1 Schematic diagram of the change of the storage modulus and loss modulus of the microcrystalline cellulose spinning solution with temperature.
[0028] Figure 2 Cross-sectional morphology of the regenerated cellulose fiber: a. -20-MeOH b. -40-MeOH c. -60-MeOH d. RT-Water schematic diagram.
[0029] Figure 3 SEM images of the regenerated cellulose fiber: a. -20-MeOH b. -40-MeOH c. -60-MeOH d. RT-Water.
[0030] Figure 4 WAXD schematic diagram of the cellulose fiber; a. WAXD curve of the cellulose fiber; b. Azimuthal scan of the 002 crystal plane; c. Peak fitting of the WAXD curve of the cellulose fiber: c1. -20-MeOH; c2. -40-MeOH; c3. -60-MeOH; c4. RT-Water.
[0031] Figure 5 Schematic diagram of the mechanical properties of the regenerated cellulose fiber.
[0032] Figure 6 Schematic diagram of the mechanical properties of straw fibers; a. Cross-sectional morphology of straw cellulose fibers; b. Scanning electron microscope image of straw cellulose fibers. Detailed implementation manners
[0033] To deeply understand the present invention, we will give a comprehensive and detailed description of it. However, the present invention has various implementation manners and is not limited to the specific examples listed herein. The presentation of these examples aims to deepen the comprehensive understanding of the disclosed content of the present invention.
[0034] Example 1
[0035] Step 1, 40 g of microcrystalline cellulose MCC is activated by water / DMAc, dissolved in 8% LiCl / DMAc, magnetically stirred at 110 °C for 50 minutes, and stirred at 5 °C for 24 hours to form an optically uniform spinning solution.
[0036] Step 3, through the gel spinning process, the solution is extruded into a -60 °C methanol bath (drawn 6 times). The spinning solution is extruded from the needle through an extrusion device, and the fine stream of the spinning solution enters the coagulation bath at different temperatures after passing through a fixed-length air layer.
[0037] Step 4, the as-spun fibers are immersed in water for 24 h, washed, and vacuum dried at 60 °C to obtain regenerated cellulose fibers. The obtained fibers have a strength of 425 MPa, a modulus of 31 GPa, and a roundness index of 0.85.
[0038] Example 2
[0039] Step 1, 10 g of straw cellulose is activated by water / DMAc and dissolved in 5% LiCl / DMAc;
[0040] Step 3, gel spinning: The solution is extruded into a -60 °C methanol coagulation bath (drawn 5 times) through the gel spinning process.
[0041] Step 4, the regenerated cellulose as-spun fibers obtained from the coagulation bath are put into water and immersed for 24 h, and finally vacuum dried at 60 degrees to obtain regenerated cellulose fiber samples; the obtained fibers: strength 664 MPa, modulus 41 GPa.
[0042] Experimental tests
[0043] I. Optimization of gel spinning parameters
[0044] 1.1 Experimental process
[0045] Before solvent treatment, the microcrystalline cellulose (MCC) powder was dried under vacuum at 60 °C until its weight remained stable. For solvent treatment with water, 40 g of MCC powder was immersed in deionized water at 30 °C for 24 hours, followed by vacuum filtration and vacuum drying at 60 °C until there was no further weight loss. Subsequently, the water-treated MCC was treated with DMAc under the same conditions as the water treatment. The LiCl / DMAc formulation was prepared by mixing 8 g of LiCl and 92 g of DMAc at 60 °C with continuous magnetic stirring for 24 hours until the solution became transparent. For the dissolution of MCC, 9 g of the pretreated MCC was slowly added to 66 g of the LiCl / DMAc solvent, and the mixture was stirred magnetically at 110 °C for 50 minutes. Then the bottle was transferred to a double-layer reactor at 5 °C and stirred mechanically for 12 hours.
[0046] 1.2 Sample preparation
[0047] The spinning process using the microcrystalline cellulose / LiCl / DMAc solution is as follows: the spinning solution is extruded from the needle through an extrusion device, and the fine stream of the spinning solution enters coagulation baths with different temperatures and types after passing through a fixed-length air layer. The regenerated cellulose nascent fibers obtained from the coagulation bath are immersed in water for 24 h and finally vacuum dried at 60 °C to obtain the regenerated cellulose fiber samples.
[0048] 1.3 Test results
[0049] Using microcrystalline cellulose as the raw material, regenerated cellulose fibers were prepared by a spinning process. The rheological properties of the microcrystalline cellulose spinning solution were studied, and the changing trends and laws of the mechanical properties, crystal structure, and orientation degree of the fibers were comparatively studied under different spinning temperatures (-20, -40, -60 °C) and different coagulation baths (low-temperature methanol, normal-temperature water). When the spinning temperature is below the gel temperature of the microcrystalline cellulose spinning solution, the spinning solution first gels and then phase-separates to form cellulose fibers. This is the gel spinning method. When the spinning temperature is above the gel temperature of the microcrystalline cellulose spinning solution, the spinning solution directly phase-separates to form cellulose fibers, which is generally called the dry-jet wet spinning method.
[0050] The similarities and differences in the fiber structure and properties between the gel spinning method and the dry-jet wet spinning method were comparatively studied during the preparation of regenerated cellulose fibers. The specific research contents and results are as follows:
[0051] A. Rheological properties of the spinning solution
[0052] We investigated the changes in the storage modulus and loss modulus of the microcrystalline cellulose spinning solution with temperature, and the obtained results are as Figure 1 shown. From Figure 1As can be seen, when the temperature of the microcrystalline cellulose spinning solution is above -35°C, the storage modulus is less than the loss modulus, indicating that the flow properties of the solution are more like those of a liquid. As the solution temperature decreases, both the storage modulus and the loss modulus increase. When the spinning solution temperature is -35°C, the storage modulus and the loss modulus are equal, indicating that the flow properties of the spinning solution are in a gel state at this time. We can define this temperature as the gel temperature point of the spinning solution. Therefore, during the spinning process, the temperature at which the fiber forms is crucial. When regenerated cellulose fibers are prepared from microcrystalline cellulose, when the fiber forming temperature is lower than the gel temperature point, the spinning solution will first form a gel and then phase-separate to form a fiber morphology. When the fiber forming temperature is higher than the gel temperature point, the spinning solution will first phase-separate to form a fiber morphology. This will provide a basis for us to determine the fiber forming temperature and also provide a basis for us to control the fiber forming process.
[0053] C. The forming process and property changes of regenerated cellulose fibers under different coagulation conditions
[0054] The cross-sectional morphology of the fibers was observed using an optical microscope ( Figure 2 ), and it was found that the fibers in the methanol coagulation bath showed better roundness at higher temperatures. At a temperature of -20°C, the cross-section of the fibers was observed to be basically circular. However, when the temperature was lowered to -60°C, the cross-sectional shape of the fibers changed to kidney-shaped.
[0055] This phenomenon may be due to the fact that at low temperatures, the coagulation layer on the fiber surface is thinner, resulting in the inward collapse of the fiber under the action of tension. On the contrary, at higher temperatures, the spinning solution coagulates quickly, thus forming a uniform circle. In the water coagulation bath, the cross-section of the fibers is also circular, but the regularity is slightly inferior to that of -20-MeOH. Although the spinning solution in water diffuses outward very quickly, the cellulose can coagulate rapidly. However, in previous studies, it was found that during the spinning process, the inward diffusion rate of water is relatively slow, resulting in uneven coagulation of cellulose.
[0056] As Figure 3 shown, in the scanning electron microscope image of the fibers, the fiber surface is smooth in the methanol coagulation bath at higher temperatures. However, as the temperature of the coagulation bath decreases, grooves appear on the fiber surface. This is due to the different coagulation rates of the spinning solution. The surface of the fiber with a slower coagulation rate will shrink during subsequent processing, thus forming grooves on the fiber surface.
[0057] We performed XRD tests on the regenerated cellulose fibers to characterize their crystalline structure. We fitted the scans of the equatorial plane and the azimuth angle of the 002 crystal plane and summarized the results in (Table 1). As Figure 4, it can be seen that the crystal plane spacing of the fibers in the water coagulation bath is significantly larger than that of the fibers in the methanol coagulation bath. In addition, the crystal size of the fibers along the axial direction in the water coagulation bath is much smaller than that of the fibers in the methanol coagulation bath. This indicates that the crystallization of cellulose in the methanol coagulation bath is denser and more complete.
[0058] Comparing the crystal data of the three kinds of fibers prepared in the methanol coagulation bath, it can be found that the differences in their crystal plane spacings are relatively small, which proves that the crystals of the fibers coagulated in the same methanol are relatively dense. In terms of crystal size, the sample marked -60-MeOH is slightly larger than the other two samples. This may be because the cellulose molecular chains in the spinning solution in the gel state are frozen and are not easily relaxed when stretched in the coagulation bath. Therefore, the molecular chains can be arranged more orderly under the action of the tensile force, resulting in larger crystals being generated along the axial direction of the fiber. The crystallinity data shows that the crystallinity of the -60-MeOH sample is about 10% higher than that of the other samples. This finding is closely related to the crystallization environment of cellulose. As mentioned above, at -60°C, the external diffusion of lithium chloride in the spinning solution is extremely small. And the ability of the DMAc / LiCl solution to dissolve cellulose depends on the concentration of lithium chloride. Therefore, the methanol coagulation bath at -60°C provides the best environment for the crystallization of cellulose, thus increasing the crystallinity of cellulose.
[0059] Table 1: Summary of crystallographic data of regenerated cellulose fibers
[0060]
[0061] Figure 5 The mechanical property data of the regenerated cellulose fibers are shown. The analyzed data clearly shows that the -60-MeOH fibers have more superior mechanical properties, with a strength 65% higher than that of the RT-Water fibers and a modulus 61% higher than that of the RT-Water fibers. In addition, based on the fact that the strength and modulus of the -60-MeOH fibers are higher than those of the -20-MeOH and -40-MeOH fibers, their elongation at break is also higher than theirs, which proves that there are fewer defects in the -60-MeOH fibers than in the other two kinds of fibers.
[0062] In summary, a) Rheological properties of the microcrystalline cellulose spinning solution: When the temperature of the spinning solution is lower than the gel temperature, the spinning solution gels. c) Fibers spun at -60°C have a more perfect surface. d) Comparison of crystal structures under two spinning methods: Although the fibers prepared by the two methods are basically the same in crystal structure, the crystal structure of the fibers prepared by the gel spinning method is denser and more perfect, which is attributed to the lower solvent diffusion rate providing milder conditions for the crystallization of cellulose. e) Change in the crystal orientation degree of regenerated cellulose fibers: The cellulose prepared by low-temperature gel spinning has a higher draw ratio and can obtain a higher orientation. f) Comparison of tensile properties: The regenerated cellulose fibers prepared by the gel spinning method are superior to the dry-jet wet spinning method in terms of tensile properties, including tensile strength and modulus.
[0063] II. Application of Gel Spinning in Straw Cellulose
[0064] 2.2.1 Experimental Procedure
[0065] A. Solution Preparation
[0066] Before solvent treatment, the straw cellulose powder was vacuum-dried at 60°C until its weight remained stable. For solvent treatment with water, 10 g of straw cellulose powder was immersed in deionized water at 30°C for 24 hours, followed by vacuum filtration and vacuum drying at 60°C until there was no further weight loss. Subsequently, the water-treated straw cellulose was treated with DMAc under the same conditions as the water treatment. The LiCl / DMAc solution was prepared by mixing 8 g of LiCl and 92 g of DMAc at 60°C with continuous magnetic stirring for 24 hours until the solution became transparent. For the dissolution of straw cellulose, 2 g of pretreated straw cellulose was slowly added to 48 g of the LiCl / DMAc solvent, and mechanically stirred at 110°C for 50 minutes, then the bottle was transferred to a double-layer reactor at 5°C and stirred mechanically for 12 hours.
[0067] B. Sample Preparation
[0068] The spinning process using the straw cellulose / LiCl / DMAc solution was as follows: The spinning solution was extruded from the needle through an extrusion device, and the spinning solution stream entered a -60°C methanol coagulation bath after passing through a fixed-length air layer. The regenerated cellulose primary fibers obtained from the coagulation bath were immersed in water for 24 h and finally vacuum-dried at 60°C to obtain regenerated cellulose fiber samples.
[0069] 2.1.2 Results and Discussion
[0070] A. Crystallographic Analysis
[0071] The fibers produced from straw cellulose show a decrease in crystallinity and crystal size, which is attributed to the lower concentration of the cellulose solution and the inhibition of cellulose crystallization. However, we found that there is a significant increase in the degree of orientation of its crystals, which is due to the fact that a higher molecular weight is conducive to the ordered arrangement of cellulose molecular chains.
[0072] B. Cross-sectional morphology and its mechanical property testing
[0073] As Figure 6 shown, the cross-section of the straw cellulose fiber is similar to that of -60-MeOH, presenting an irregular kidney-shaped morphology with a roundness index of 0.80. The surface of the rice straw cellulose fiber is smoother than that of the fibers in previous studies, but there are still some uneven parts, which are caused by surface wrinkling. Generally speaking, the surface and cross-sectional morphology of the fiber are consistent with those of -60-MeOH. Tensile testing shows that the strength of the fiber is 664 MPa and the modulus is 41 GPa. The mechanical properties of the fibers produced from straw cellulose are significantly better than those of viscose fibers currently sold on the market. The tensile strength of these fibers can reach the level of Modal fibers, while the elastic modulus is much greater than that of the fibers described on the market and is comparable to that of Ioncell fibers.
[0074] In summary, a) the crystallinity of cellulose will decrease when the concentration of the spinning solution is low; b) higher molecular weight cellulose is conducive to forming higher orientation and a more complete surface; c) low-temperature gel spinning also has advantages in high molecular weight cellulose raw materials; d) the change in the degree of crystal orientation of regenerated cellulose fibers: the cellulose prepared by low-temperature gel spinning has a higher draw ratio and can obtain higher orientation; e) comparison of tensile properties: the mechanical properties of the fibers produced from straw cellulose are significantly better than those of viscose fibers currently sold on the market. The tensile strength of these fibers can reach the level of Modal fibers, while the modulus is comparable to that of Ioncell fibers.
[0075] The content not described in detail in the specification of the present invention belongs to the prior art well-known to those skilled in the art. Although the illustrative specific embodiments of the present invention are described above for the convenience of those skilled in the art to understand the present invention, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the appended claims, these changes are obvious, and all inventions and creations using the concept of the present invention are within the scope of protection.
Claims
1. A preparation method of regenerated cellulose fiber based on gel spinning, characterized in that: It includes the following steps: Step 1: Activate the cellulose raw material with a water / DMAc double solvent and then dissolve it in a LiCl / DMAc system to form a spinning solution with a concentration of 5 - 15 wt%. Step 2: Extrude the solution through a gel spinning process into a methanol coagulation bath with a temperature lower than the gel point of the spinning solution, and the draw ratio is ≥3 times. Step 3: Subject the as - spun fiber to solvent replacement, washing, and drying to obtain regenerated cellulose fiber.
2. The preparation method of a regenerated cellulose fiber based on gel spinning according to claim 1, characterized in that: The cellulose raw material is selected from microcrystalline cellulose MCC or straw cellulose; A spinning solution with a concentration of 5 - 15 wt% is formed, where: the concentration of the microcrystalline cellulose spinning solution is 8 - 12 wt%, and when the draw ratio is 3 times, the fineness is ≤10.81 dtex; the concentration of the straw cellulose spinning solution is 4 - 6 wt%.
3. The preparation method of a regenerated cellulose fiber based on gel spinning according to claim 1, characterized in that: In Step 2, the temperature of the coagulation bath is -60 °C, the surface roughness Ra of the fiber is ≤0.2 μm, and the roundness index of the cross - section is ≥0.
80.
4. The preparation method of a regenerated cellulose fiber based on gel spinning according to claim 1, characterized in that: In Step 1, the mass ratio of LiCl to DMAc in the LiCl / DMAc system is 1:11.
5.
5. The regenerated cellulose fiber based on gel spinning prepared by the preparation method according to any one of claims 1 - 4, characterized in that: Microcrystalline cellulose fiber: Tensile strength is 368 - 426 MPa, modulus is 26 - 31 GPa; Straw cellulose fiber: Tensile strength ≥664 MPa, modulus ≥41 GPa.
6. The regenerated cellulose fiber based on gel spinning according to claim 5, wherein: The 002 crystal plane spacing of the regenerated cellulose fiber is ≤0.396 nm, the crystal size is ≥38 nm, and the elongation at break is ≥5%.
7. The regenerated cellulose fiber based on gel spinning according to claim 5, characterized in that: The tensile strength of the fiber is ≥350 MPa, especially the tensile strength of the straw cellulose reaches 664 MPa, the modulus is ≥18.5 GPa, the crystallinity is ≥63%, and FWHM ≤21.76°.
8. Application of the regenerated cellulose fiber based on gel spinning prepared by the preparation method according to any one of claims 1 - 4 in high - strength composite materials.
9. Application of the regenerated cellulose fiber based on gel spinning prepared by the preparation method according to any one of claims 1 - 4 in aerospace structural reinforcements.
10. Application of the regenerated cellulose fiber based on gel spinning prepared by the preparation method according to any one of claims 1 - 4 in biomedical sutures.
Citation Information
Patent Citations
Method of using non-adhesive method to prepare cellulose base fiber
CN101550614A
Microcrystalline cellulose-chitosan fiber
CN102277650A
Preparation method of acetyl cellulose hollow fiber nano filter membrane
CN102389718A
Cellulosic fiber processing
CN112805419A
Preparation method of low-cost, green and high-strength cellulose / chitosan composite regenerated fiber
CN116657276A
Cited By
Preparation method of aerogel fiber and use
US12595593B2
Preparation method of aerogel fiber and use
US20250101637A1
